DESCRIPTION OF A CLINICAL CASE OF TREATMENT OF A PATIENT WITH DISTAL OCCLUSION, TAKING INTO ACCOUNT THE VERTICAL COMPONENT OF JAW GROWTH - Rasulova Shakhnoza Rasulzhanovna; Nasimov Elbek Elkhonovich; Aripova Gavkhar Erkinovna; Arifdjanova Madinaxon Abdug’ofur qizi (American Journals Publishing, 2024)
The aim of our study was to observe and identify the features of the course during treatment with the Twin-Block apparatus in a patient with distal occlusion, taking into account the growth of the jaw bones.Research material. We examined 10 patients with distal occlusion of the dentition at the age of 9 to 12 years. 1 patient was selected, aged 10 years. Clinical, anthropometric, photometric were used, cephalograms were studied in the lateral projection.Results. In a patient with a distal occlusion and a tendency to a horizontal type of growth, with a low angle and counterclockwise rotation of the lower jaw before treatment, the cephalometric data of the Kim analysis were APDI 78.5, ODI 76.8, CF 155.3, respectively. (Fig. 2a). Treatment tactics were chosen based on the analysis of anthropometric, cephalometric and photometric data. The treatment was carried out using the Twin Block apparatus. As you know, when wearing a Twin-block, we expect a deepening of the Spee curve, and we prescribe this device, most often with a vertical type of jaw growth, with a reverse Spee curve, but knowing all the features of the patient's bone structure, their direction of growth and possible side effects from the Twin-block apparatus, we were able to prevent the predicted deviations.Conclusion. Thus, by assigning the Twin Block apparatus with a horizontal type of jaw growth and following the orthodontist's stage-by-stage actions,
Keywords: Distal occlusion, Twin-block apparatus, class II anomalies.